‘This strange little floating world of ours’: shipboard periodicals and community-building in the ‘global’ nineteenth century - Schmidt, Johanna de (Journal of global history, 2016)
Publishing a newspaper was a popular undertaking for passengers aboard intercontinental vessels during the nineteenth century. Although in almost complete isolation for weeks or even months, many travellers saw the need to issue a regular periodical. This article sheds light on the functions that these publications had for the ships’ on-board communities. On the one hand, passengers used them to inculcate a sentiment of togetherness, no matter how ephemeral their community might initially appear. On the other, the periodicals also served to separate and create boundaries between different groups of individuals aboard. Focusing on these unique historical sources allows us to study the building and dissolving of a community feeling in transit in this era of globalizing intercontinental travel. This article shows that ship newspapers were simultaneously a space for social exchange and a means of establishing social boundaries at sea in an age of increasing global shipboard travel.